The Influence of Affiliates in Product Promotion on Consumer Buying Interest - Dimas Aji Wardana; Ahmad Ramadhan (Business Finence Analyst Co.,, 2025)
The rapid development of knowledge and technology today has brought significant changes to the sales process. Digitalization, particularly in the form of online sales, has simplified transactions and required sellers to implement the latest strategies and innovations to attract buyers. One strategy that can be applied is utilizing Affiliators through Affiliate Marketing techniques to promote products. The involvement of Affiliators in online buying and selling has a considerable impact. This study focuses on this phenomenon using internet research and literature review methods. These methods will collect data from various sources, including journals, articles, and other relevant references. The research results indicate that Affiliate Marketing, carried out by Affiliators with the support of social media marketing, positively impacts online sales by increasing consumer purchase interest